Notes on taxonomy of the genus Mitreola L. (Loganiaceae) in the flora of Vietnam with a newly recorded Mitreola sphaerocarpa - Tran, Thi Phuong Anh; Le, Tuan Anh; Nguyen, Khang Sinh; Tran, Duc Binh; Nguyen, Thi Trung (Academia Journal of Biology, 2024)
Mitreola sphaerocarpa (Loganiaceae), a species occurring in Peninsular Malaysia, is newly reported for the flora of Vietnam. The description, photographs, information on ecology, preliminary conservation status and taxonomic notes are also presented. In order to facilitate identification, we provide an identification key and checklist for the 4 known Mitreola species in Vietnam.